(untitled) (Medical Forum Monthly, 2022)
Objective: We aimed to assess the prevalence of overactive bladder among women of reproductive age in our set-up. We also sought to establish its association with the commonly recognized risk factors of age, high BMI and multiparty. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the out-patient department of Obstetrics and Gynaecology Unit 1 of Dr. R K Pfau Civil Hospital Karachi from August 2019 to February 2020. Materials and Methods: Women were included if they experienced any signs/ symptoms of urinary frequency, urgency, or incontinence. To make a diagnosis of overactive bladder, detailed clinical history and examination were followed by blood and urine investigations and a pelvic ultrasound to rule out alternative diagnoses. Chi square test was run to assess the relation between overactive bladder and risk factors such as BMI , parity, and age. A P value of <0.05 was considered significant. Results: The mean age of 171 women was 30.7±7.8 years and 55.5% of them were multiparous. Overactive bladder was diagnosed in 38.6% presenting with urinary frequency (48.5%), urgency (50.3%), and nocturia (10.5%). We found no significant association between the occurrence of overactive bladder and advancing age, multiparty or high BMI. Conclusion: Overactive bladder is frequently encountered among women of reproductive age who are experiencing any urinary signs or symptoms. Further risk factors should be explored in our population. It is pertinent to specifically enquire about such symptoms in every parous woman attending a gynaecology clinic so that lifestyles modifications and management could be advised accordingly.